2011
DOI: 10.12693/aphyspola.120.950
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chemical Composition of Liquid Phase and Growth Process on Physical Properties of Bi2Se3, Bi2Te3and Bi2Te2Se Compounds

Abstract: We studied synthesis and crystal growth of Bi2Te3, Bi2Se3 and Bi2Te2Se compounds by means of vertical Bridgman method. Crystals were grown from stoichiometric melts and under different molar ratio of Bi:Te, Bi:Se or Bi:Te:Se. The obtained crystals were characterized by X-ray diffraction analysis, energy dispersive X-ray spectroscopy, scanning electron microscopy, atomic force microscopy, and the Hall effect measurements. Some of the samples demonstrated insulating bulk behavior, by means of resistivity versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Hall measurements58 yield a bulk hole density of 1.34 × 10 17  cm −3 and a mobility of 275 cm 2  V −1  s −1 . Using these values, the effective mass inferred from ARPES data and the Drude formula, we extract a velocity relaxation time of 18 fs in the bulk material.…”
Section: Methodsmentioning
confidence: 99%
“…Hall measurements58 yield a bulk hole density of 1.34 × 10 17  cm −3 and a mobility of 275 cm 2  V −1  s −1 . Using these values, the effective mass inferred from ARPES data and the Drude formula, we extract a velocity relaxation time of 18 fs in the bulk material.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore grew a series of Bi 2+x Te 2−x Se crystals, with a maximum x of 0.06, by the classic Bridgeman-Stockbarger method. 25,34 The boules obtained in these growths are approximately 14 cm in length and 0.6 cm in diameter. Due to the chemical composition distribution that naturally occurs along crystal boules during such growth, the electrical properties at different positions in the boules are expected to be different.…”
Section: B Characterization Of Transportmentioning
confidence: 98%
“…Some studies have suggested the presence of a unique Bi 2 Te 2 Se phase,9, 11 and, by thermal quenching from high temperature, it is possible to produce single‐phase Bi 2 Te 2 Se crystals with the disordered structure preserved 9. Other studies indicate that the Bi 2 Te 2 Se “phase” may in reality be a mixture of phases, as indicated by the broadening of powder X‐ray diffraction (PXRD) peaks of Bi 2 Te 2 Se, compared with those of Bi 2 Te 3 12. Due to the importance of Bi 2 Te 2 Se in both the thermoelectric and TI fields, we have undertaken a thorough characterization of the Bi 2 Te 2 Se single crystals grown by the Stockbarger method, to obtain a clear understanding of the composition, structure, defects, and properties.…”
Section: Elemental Composition (Icp‐aes) Of Bi2texsey At Different Pomentioning
confidence: 99%